Feasibility and clinical outcome of rotational atherectomy in patients presenting with an acute coronary syndrome. Issue 3 (9th September 2018) - Allali, Abdelhakim; Abdelghani, Mohammad; Mankerious, Nader; Abdel‐Wahab, Mohamed; Richardt, Gert; Toelg, Ralph
Abstract: Objectives: We aimed to investigate the feasibility, safety, and outcome of rotational atherectomy (RA) in the setting of acute coronary syndrome (ACS). Background: Limited data are available on the use of RA in patients presenting with ACS. Methods: This analysis is from an observational registry, which enrolled all consecutive patients undergoing RA in a tertiary center. Between 2002 and 2015, 433 patients with stable coronary artery disease (SCAD) were treated with RA. Within the same period, 108 patients with ACS (8 STEMI and 100 NSTE‐ACS) were treated with RA. Procedural success was similar between the ACS and the SCAD groups (96.6% vs. 96.4%, P = 0.90), and no significant difference was observed in procedural complications (slow‐flow: 0.8% vs. 2.8%, P = 0.32; coronary dissection: 6.8% vs. 7.2%, P = 1.00; coronary perforation: 0.8% vs. 1.7%, P = 0.69). In‐hospital MACE rates were comparable (3.7% vs. 3.2%, P = 0.77). The risk of MACE within 24 months was higher in ACS patients (39.9% vs. 22.4%, log‐rank P = 0.002; HR: 1.39; 95% CI: 1.12–1.73; P = 0.003). Multivariable Cox regression analysis identified left ventricular ejection fraction (HR 0.97; 95% CI: 0.85–0.99; P = 0.001), treatment with a BMS (HR 2.22, 95% CI: 1.15–4.25, P = 0.02) or early generation drug eluting stent (HR 1.99; 95% CI 1.09–3.64; P = 0.03), as well as ACS presentation (HR 1.53; 95% CI: 1.02–2.29; P = 0.04) as predictors of MACE at two years. Conclusions: RA is technically feasible and safe in high risk patients presenting with ACS. However, successful application of RA did not mitigate the higher rate of long term cardiovascular events.